MicroRNA‐425‐3p predicts response to sorafenib therapy in patients with hepatocellular carcinoma. (21st July 2014) - Vaira, Valentina; Roncalli, Massimo; Carnaghi, Carlo; Faversani, Alice; Maggioni, Marco; Augello, Claudia; Rimassa, Lorenza; Pressiani, Tiziana; Spagnuolo, Gaia; Di Tommaso, Luca; Fagiuoli, Stefano; Rota Caremoli, Elena; et al.
Abstract Background & Aims Sorafenib is the standard of care in advanced hepatocellular carcinoma (HCC), however no criteria have been established to select patients likely to benefit from this therapy. In this study, we evaluated the predictive role of microRNAs (miRNAs) in this setting of patients. Methods We profiled 522 miRNA in a series of 26 HCC patients treated with sorafenib (training set) and validated the results in an independent series of 58 patients (validation set). Formalin‐fixed paraffin‐embedded tumour and cirrhotic liver biopsies were used for RNA extraction and miRNAs profiling with TaqMan Arrays technology. Statistical analyses were used to correlate miRNA levels with clinical outcome, including time to progression (TTP), progression free (PFS), and overall survival. Cell viability and cell motility of HuH‐7 or HepG2 HCC cells were tested in vitro after transfection with specific miRNA precursor, inhibitor or controls and sorafenib treatment. Results Six miRNAs were significantly associated with clinical variables in the training set and only miR‐425‐3p could be further validated. Higher levels of miR‐425‐3p were associated with longer TTP and PFS (P = 0.0008; HR = 0.4; 95% CI = 0.2–0.7 and P = 0.007; HR = 0.5; 95% CI = 0.3–0.9 respectively). Multivariate analysis confirmed the predictive significance of miR‐425‐3p. Furthermore, an association between increased miR‐425‐3p, cell death and reduced cell motility was defined in vitro in HCC cell lines treated with sorafenib. Conclusions Assessment of miR‐425‐3p levels in liver biopsies could help in stratifying patients with advanced HCC for sorafenib treatment. These promising results need to be confirmed in a large prospective study.